Modification of the metro rolling stock maintenance process, taking into account the condition of selected vehicle components - Marek Sokołowski (Przegląd Komunikacyjny)
Abstract: The article covers the possibilities of using modern IT and electronic solutions to modify the maintenance process of railway vehicles operated in the Warsaw metro. The legal and technical aspects of rolling stock operation were discussed, and examples of three types of vehicles used in the Warsaw Metro were presented. The current technical solutions in the field of monitoring the condition of some vehicle components were indicated. Keywords: Metro; Rolling stock; Maintenance system